2014
DOI: 10.1016/j.ypmed.2013.11.006
|View full text |Cite
|
Sign up to set email alerts
|

The lower quality of preventive care among forced migrants in a country with universal healthcare coverage

Abstract: OBJECTIVE: To assess the association between socio-demographic factors and the quality of preventive care and chronic care of cardiovascular (CV) risk factors in a country with universal health care coverage. METHODS: Our retrospective cohort assessed a random sample of 966 patients aged 50-80years followed over 2years (2005)(2006)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…Patients are free to choose their primary care physician (PCP). However, high quality of care might not be fully explained by health insurance status only; we have recently found that both forced migrants and undocumented migrants in Switzerland had lower quality of preventive care, albeit forced migrants have health care coverage and undocumented migrants do not [35].…”
Section: Discussionmentioning
confidence: 90%
“…Patients are free to choose their primary care physician (PCP). However, high quality of care might not be fully explained by health insurance status only; we have recently found that both forced migrants and undocumented migrants in Switzerland had lower quality of preventive care, albeit forced migrants have health care coverage and undocumented migrants do not [35].…”
Section: Discussionmentioning
confidence: 90%
“…Other cantons either delegate this task to nongovernmental organizations (NGO) or offer no service at all, apart from access to the emergency department of public hospitals. Consequently, undocumented migrants receive less preventive healthcare than other groups of the population and management strategies for those with chronic disease are lacking in regions without dedicated primary care programs [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Type 2 diabetes prevalence is rather low in Switzerland compared to neighboring countries [ 13 ]. Even when accessing to care and with insurance coverage, vulnerable immigrants are less likely to receive preventive measures for cardiovascular risk factors, including diabetes [ 14 ]. Moreover, insured diabetics from lower socio-economic status in Switzerland receive lower quality of care and have poorer outcomes, adding to similar inequalities found in patients with other chronic health conditions [ 13 , 15 17 ].…”
Section: Introductionmentioning
confidence: 99%